1985
DOI: 10.2166/wst.1985.0104
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Biotic and Abiotic Factors and Viruses in a Water System

Abstract: A river intensively used along its entire course for extracting potable water and for discharging domestic and industrial effluents permanently carries a high load of viruses, including hepatitis A and rotaviruses. In the areas supplied with potable water from this river hepatitis A is endemic. The river has been investigated four times at 16 or more sampling points throughout its course in the years 1981, 1982 and 1983. Coincident with the virological investigation, biological, microbiological and chemical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Cliver and Herrman (1972) tested six bacterial species and found only Bacillus subtilis and Pseudomonas aeruqinosa gave firm evidence of antiviral activity against Coxsackie virus A9. Walter et al (1985) report that cyanobacteria and algae are capable of inactivating enteric viruses. Cheo (1980) found that tobacco mosaic viruses were relatively stable in sterile soils, but were rapidly inactivated when placed in a nonsterile soil environment.…”
Section: Inactivation Mechanismsmentioning
confidence: 99%
“…Cliver and Herrman (1972) tested six bacterial species and found only Bacillus subtilis and Pseudomonas aeruqinosa gave firm evidence of antiviral activity against Coxsackie virus A9. Walter et al (1985) report that cyanobacteria and algae are capable of inactivating enteric viruses. Cheo (1980) found that tobacco mosaic viruses were relatively stable in sterile soils, but were rapidly inactivated when placed in a nonsterile soil environment.…”
Section: Inactivation Mechanismsmentioning
confidence: 99%
“…The ability of aluminum hydroxide and other metallic precipitates to efficiently adsorb viruses has led to their use in methods for the recovery of viruses from water. Aluminum hydroxide flocs have been used as the virus adsorbent in the first or second stages of virus concentration procedures (6,28). Preformed magnesium hydroxide flocs have been used to further concentrate viruses eluted from microporous filters (24).…”
mentioning
confidence: 99%